Leadership of Private Islamic Universities Perspective Management Theory of Educational Institution Management - Musa Musa (Journal Research of Social Science, Economics, and Management, 2022)
For leadership management, education cannot run perfectly if education management is not implemented properly, in various theories and legislation clearly regulates the role of educational institutions, especially education run by private universities, these rules are the main point to be read and understood. This research was conducted with the aim of knowing how the leadership management of private universities is in terms of institutional management theory. This study uses library research methods or literature research. Data collection techniques in this study were carried out by collecting and analyzing primary data sources from books, articles, and research results related to the problems discussed. The results of the study conclude that leadership means the ability to influence others with various types of leadership with their advantages and disadvantages, with quality Islamic higher education leadership and guided by the rules made by the government will create quality higher education, because quality education is seen as a means of and infrastructure for higher education is considered a quality campus that produces quality students as well